Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

wonder

  • 3 years ago

If f(x) = x2 − 2x + 9 and g(x) = 8 − x, what is (f o g)(−4)?

  • This Question is Closed
  1. rahulchatterjee
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    fog(x)=f(g(x)) =f(8-x) =(8-x)^2-2(8-x)+9 =(64+x2-16x)-16+2x+9 =x2-14x+57 now fog(-4)= put the value of x as -4...

  2. pratu043
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Please ask in the math section.

  3. TranceNova
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Hi please post questions in the correct section :)

  4. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy